O Sistema de Avaliação da Educação Básica (Saeb) e seus efeitos no trabalho docente nos anos iniciais do ensino fundamental da rede estadual de educação de Uberlândia/MG - Silva, Graciele Alves da (2024)
This investigation is part of the research line State, Policies and Management in Education, of the Graduate Program in Education, from Faculty of Education of Federal University of Uberlândia (PPGED/FACED/UFU, in Portuguese abbreviation). As an object of investigation, we delimited public external evaluation policies, specifically the Basic Education Assessment System (SAEB), with the aim of analyzing the effects of this system on teaching work, from the perspective of teachers working in the 5th grade of Elementary School in the state education network in the city of Uberlândia, Minas Gerais, Brazil. The specific objectives are: to understand the concepts that guide public evaluation policies according to the logic of neoliberal State; characterize assessment policies, centrally new Saeb, impacted by the National Common Curricular Base (BNCC); characterize teaching work based on bibliographical study; investigate how teachers in the early years of Elementary School analyze and use the results obtained from external assessments; and identify the teachers’ perspective on external evaluation policies in relation to the aforementioned system. Regarding methodological aspects, we adopted a qualitative approach, as it enables the advancement of knowledge in education and contributes to the understanding of processes that permeate the contexts of educational policy focused on this study. In this context, we adopted a bibliographical research to deepen the theory underlying the study and support the analysis of data obtained from the Brazilian Digital Library of Theses and Dissertations (BDTD), in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Personnel and Higher Education (CAPES) and in the repository of UFU. In the empirical field, we developed questionnaires to understand the working conditions of teachers who work in different institutions in the education network investigated; understand the view of these professionals about Saeb; and evaluate its effects on teaching work. To this end, the research is based on authors such as Afonso (2000, 2009a, 2009b, 2010, 2013, 2018), Dardot and Laval (2016), Freitas (2004, 2007, 2012a, 2012b, 2012c, 2018, 2020, 2023), Gentili (1996), Harvey (2008, 2012), Laval (2019), Richter (2015) and Saviani (2007a, 2007b, 2010, 2016). It should be underlined that educational policies for external assessments, in accordance with the neoliberal model, value competition, efficiency and the search for measurable results. From the 1990s onwards, the principles of this bias directly impacted Brazilian education, which led the State to assume a central role in the evaluation of educational policies and projects in all modalities and levels of education. In terms of results, we found that, with the proposals of new Saeb, preparatory activities for external assessments were intensified, especially in the subjects of Portuguese and Mathematics, which highlighted with the workload addition, according to the interviewed subjects. In this context, demands and accountability for results increase and interfere on teaching work, by affecting the professional’s autonomy in the classroom; preclude the fulfilment of the planning made by te teacher; and generate overload, which demands more working time.